Providing Economic Security of Enterprises Through Sindinic as Science of Danger - A. A. Dokukina (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Against a background of opportunities opened to business in times of innovation economy we can observe growing risks connected with specific features of information flows, technologies of transaction handling and new approaches in management. Due to these factors the author studies a model depicting parameters and characteristics of processes providing economic security of enterprises and possibilities of its application in practice. The article substantiates the assumption about expediency of using sindinic principles in managing the enterprise with regard to the current requirements to the level of economic security. The author puts forward the approach to using 5D model of sindinic in management of industrial enterprises, as well as innovation systems as a solution aimed at developing and retaining its competitive features in active interaction with external environment.